Nobiletin regulates invasion, migration and metastasis in hypopharyngeal squamous cell carcinoma. : Nobiletin regulates oral cancer - Rosas-Martínez , Marisol; González Rosales, José Antonio; Gutiérrez-Venegas, Gloria (Cellular and Molecular Biology, 2023)
Head and neck squamous cell carcinoma carries a poor prognosis. Patients typically present with advanced disease and exhibit severe malnutrition at the time of diagnosis. Nobiletin (NOB) (5,6,7,8,3’,4’-Hexamethoxyflavone) is a polymethoxyflavone that inhibits the proliferation and migration of various cancer cell types. To the best of our knowledge, its effects on hypopharyngeal squamous cell carcinoma have not been evaluated previously. This study examined the effects of NOB on the proliferation, migration, and invasiveness of the FaDu cell line derived from hypopharyngeal squamous cell carcinoma. We determined protein kinase phosphorylation by western blot analysis, migration by Transwell assay, and metastatic potential by enzyme-linked immunosorbent assay of vascular endothelial growth factor. NOB inhibited cell proliferation by 40% at concentrations of 15 µM and 40 µM, and reduced migration and induced apoptosis at 50 µM by downregulating extracellular signal–regulated kinase, protein kinase B, and phosphoinositide 3-kinase. Our results suggest that the effects of NOB on FaDu cells are associated with protein kinase inhibition.